Examining the Awareness Levels, Usage Trends, and Influencing Factors of Emergency Contraceptives Among Women in Ussa Local Government Area of Taraba State, Nigeria: A Cross-Sectional Research Inquiry - Andeskebtso Yohanna Adaki; Jellason Yinalabi Anthony; Megia Esvandiari (Research Synergy Foundation, 2023)
Unintended pregnancies and unsafe abortions remain significant global public health concerns, particularly in low-income countries. This research assessed the awareness, usage, and influencing factors of emergency contraceptives among women in the Ussa Local Government Area of Taraba State, Nigeria. The study employed a cross-sectional survey research design where 384 questionnaires were distributed among sampled women of the reproductive age group (15-49 Years) in the study area. The findings indicate that while roughly half of the respondents were aware of emergency contraceptives, there is room for improvement in terms of disseminating information about their availability and usage. Regarding the usage of emergency contraception, a sizable portion of respondents (34.3%) said they had used it, although the majority (65.7%) had not. Furthermore, formal sensitization on emergency contraceptives is lacking for a large part of the population, just as a significant proportion of respondents have yet to use them. The study also found that factors influencing women's attitudes toward emergency contraceptives in Ussa Local Government Area include economic constraints, knowledge gaps, moral beliefs, partner dynamics, social stigma, and the fear of negative health implications. Based on the findings of the study, the recommendations include enhancing health promotions by Health agencies in Ussa Local Government, encouraging parent-child discussions on reproductive health, engaging traditional and religious leaders in family planning promotions, establishing young girls-friendly centers, and implementing comprehensive reproductive health education programs to empower women and reduce unintended pregnancies.